Brand auditing and the development of the brand salience management model of the Statistics Study Program - Deddy A. Suhardi; Adhi Susilo; Sony Heru Priyanto; Antonius Surya Abdi (Journal of Innovation and Entrepreneurship, 2022)
This research contains a novelty in producing a study program brand audit method and developing a brand salience development model in higher education, which has not been widely discussed. A quantitative-explanative research method was used in this study by collecting online survey data on the potential market for the Statistics Study Program with a total of around 1000 people from all over Indonesia, which is related to the understanding, association, perception, experience, brand equity, and consumer brand salience towards the Statistics Study Program. The data were analyzed using structural equation modeling (SEM). The results obtained are the formulation of a brand audit model and a salience brand management model for the Universitas Terbuka Statistics Study Program.
Keywords: 650; Brand salience; Branding; SEM; Statistics Study Program; Universitas Terbuka